Synthesis of 2,2-difluoro-1,3-diketone and 2,2-difluoro-1,3-ketoester derivatives using fluorine gas - Hampton, Alexander S.; Hodgson, David R. W.; McDougald, Graham; Wang, Linhua; Sandford, Graham (Beilstein Journal of Organic Chemistry, 2024)
Solutions of 1,3-diketones and 1,3-ketoester derivatives react with fluorine to give the corresponding 2,2-difluoro-1,3-dicarbonyl derivatives in the presence of quinuclidine. Quinuclidine reacts with fluorine in situ to generate a fluoride ion that facilitates limiting enolization processes, and an electrophilic N–F fluorinating agent that is reactive towards neutral enol species.
Keywords: difluorination; difluoromethylene; direct fluorination; electrophilic fluorination; organofluorine